Quality of Life and Sexual Distress in Women With Erosive Vulvovaginal Lichen Planus. Issue 2 (April 2017) - Cheng, Harriet; Oakley, Amanda; Conaglen, John V.; Conaglen, Helen M.
Abstract : Objectives: Erosive vulvovaginal lichen planus (EVLP) is a chronic and painful genital dermatosis. Little is published about its impact on quality of life. This study aimed to evaluate quality of life and sexual function in women with EVLP. Materials and Methods: Women with genital dermatoses were surveyed using the Dermatology Life Quality Index (DLQI) and Hospital Depression and Anxiety Scales. A subgroup completed the Female Sexual Distress Scale and Female Sexual Function Index subscales. Patient characteristics including age, diagnosis, and current treatment were recorded. Results from women with EVLP were compared with other diagnoses. Results: Data from 77 women who participated between March 2013 and March 2014 were analyzed. Of these, 17 had EVLP. Comparator groups included women with vulval lichen sclerosus ( n = 48) and vulval dermatitis ( n = 12). In women with EVLP, 59% reported at least moderate impact on quality of life; mean DLQI scores: EVLP, 7.18; lichen sclerosus, 3.79; dermatitis, 8.67; p = .008. Overall, scores suggested depression in 14% and anxiety in 16% of participants. Sexual distress scores 11 or higher were recorded by 69% of women with EVLP, 63% of women with lichen sclerosus, and 56% of women with dermatitis. In those completing all sections of the survey ( n = 40), DLQI was significantly correlated with depression ( p = .004), sexual distress ( p = .001), and sexual satisfaction ( p = .01). Conclusions: Sixty-nine percent of women with EVLP reported sexual distress. Women with EVLP reported lesser quality of life than those with lichen sclerosus. Quality of life, anxiety and depression, sexual distress, and sexual function were all related in these participants. Abstract : Sixty-nine percent of women with erosive vulvovaginal lichen planus reported sexual distress; their quality of life was less than in women with lichen sclerosus.